An updated checklist of the vascular flora native to Italy. (4th March 2018) - Bartolucci, F.; Peruzzi, L.; Galasso, G.; Albano, A.; Alessandrini, A.; Ardenghi, N. M. G.; Astuti, G.; Bacchetta, G.; Ballelli, S.; Banfi, E.; Barberis, G.; Bernardo, L.; et al.
Abstract: An updated inventory of the native vascular flora of Italy, providing details on the occurrence at regional level, is presented. The checklist includes 8195 taxa (6417 species and 1778 subspecies), distributed in 1092 genera and 152 families; 23 taxa are lycophytes, 108 ferns and fern allies, 30 gymnosperms and 8034 angiosperms. The taxa currently occurring in Italy are 7483, while 568 taxa have not been confirmed in recent times, 99 are doubtfully occurring in the country and 19 are data deficient. Out of the 568 not confirmed taxa, 26 are considered extinct or possibly extinct.